Phenology of four native fruit-tree species of the "cerrado" region of Selvíria, MS, Brazil - Bianco, Silvano; Pitelli, Robson Antônio (Pesquisa Agropecuaria Brasileira, 2014)
This research was carried out from May 1, 1980 to April 31, 1981, under the edaphological conditions of Selvípia, MS, Brazil, to determine blossoming and fruiting periods of "mangaba" (Hancornia speciosa Gomes), "pequi" (Caryocar brasiliense Camb.), marolo (Annona crassiflora Mart.), and "araticum" (Annona coriacea Mart.). Ten plants of each species were studied. Flowering of these species was obtained at the beginning of the rainy season, with the exception of Hancornia speciosa Gomes. The differences in the blossoming and fruiting periods of Caryocar brasiliense Camb., Annona crassiflora Mart. and Annona coriacea Mart. appear to be related to the edaphoclimatic conditions of the region.